2016
DOI: 10.1002/jsfa.7671
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative evaluation of kernel anthocyanins from southwestern United States blue corn

Abstract: Quantitative and qualitative anthocyanin expression was determined to be relatively stable across multiple southwestern environments. Increased expression of red and purple pigmentation in accession Flor del Rio appeared to be associated more with reduced TAC and cyanidin 3-glucoside than with elevated pelargonidin per se. A previously unreported anthocyanin component in blue corn, cyanidin 3-disuccinylglucoside, is present in southwestern landraces. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 30 publications
7
46
0
4
Order By: Relevance
“…Santa Clara Blue, Los Lunas High, and Hopi Blue (highest proportions of violet blue 92A and blue 103A colored samples) displayed the highest amounts of cyanidin and pelargonidin, and Flor del Rio (primary classification red purple 59A) displayed the lowest. Similar observations have been made in other studies (Cevallos‐Casals and Cisneros‐Zevallos 2003; Moreno et al 2005; Jing et al 2007; Lopez‐Martinez et al 2009; Nankar et al 2016a). Conversely, Yang et al (2009) reported that purple maize kernels contained more anthocyanin than blue and red kernels.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Santa Clara Blue, Los Lunas High, and Hopi Blue (highest proportions of violet blue 92A and blue 103A colored samples) displayed the highest amounts of cyanidin and pelargonidin, and Flor del Rio (primary classification red purple 59A) displayed the lowest. Similar observations have been made in other studies (Cevallos‐Casals and Cisneros‐Zevallos 2003; Moreno et al 2005; Jing et al 2007; Lopez‐Martinez et al 2009; Nankar et al 2016a). Conversely, Yang et al (2009) reported that purple maize kernels contained more anthocyanin than blue and red kernels.…”
Section: Discussionsupporting
confidence: 92%
“…TAC values in this study were similar to those reported by Nankar et al (2016b), in which different anthocyanin analysis methods were used. Results reported for TAC from this study were relatively higher but were not significantly different from an analysis of samples obtained in 2012 Nankar et al (2016a). These results clearly show the consistency and stability in TAC across different years and analytical methods.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations